Early Warning and Rapid Response System for Pests and Diseases. An Operational Guide - Michael Osae (2024)
The increasing threat of pests and diseases poses significant challenges to agricultural productivity and food security in Ghana. This handbook on the Early Warning and Rapid Response System for Pests and Diseases (EWRRS-PD) developed through efforts under the Accelerating Impact of CGIAR Climate Research in Africa (AICCRA) aims to provide a comprehensive framework for stakeholders involved in pest management, including farmers, agricultural extension workers, policymakers, and researchers. The EWRRS-PD is designed to enhance the capacity for early detection and prompt response to pest outbreaks, thereby mitigating potential losses in crop yields and safeguarding livelihoods.